Analisis Efektivitas Pengendalian Temperatur Ruang Produksi menggunakan Pendekatan Kaizen dengan Siklus PDCA - Perdian Syah; Agus Suwarno; Annisa Syahliantina (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
The physical work environment in the Aerosol Production Department of PT XYZ experienced problems related to excessive room temperatures reaching 37.3°C and chemical odor pollution caused by vapor recirculation from the coating oven process. These conditions potentially reduced operator comfort and concentration. This study aimed to analyze the effectiveness of the Kaizen approach through the Plan-Do-Check-Act (PDCA) cycle in controlling production room temperature and improving air quality. A quantitative descriptive method with an Action Research approach was employed. Problem identification and root cause analysis were conducted using the 7 QC Tools, particularly the Pareto Diagram and Fishbone Diagram. Improvement actions included the installation of turbine ventilators, aluminum foil roof insulation, and a 3-meter vertical exhaust ducting system. The results showed that the average room temperature decreased from 34.6°C to 27.4°C, representing a reduction of 7.2°C, while the peak daytime temperature decreased by 8.7°C and met the established threshold limit value. In addition, chemical odor pollution was completely eliminated. Therefore, the Kaizen-PDCA approach proved effective in improving the physical work environment sustainably.